A rare case of basilar impression. (1st June 2012) - Verma, Rajesh; Junewar, Vivek; Garg, Ravindra Kumar; Malhotra, Hardeep Singh
Abstract : A teenage girl presented with progressively worsening neck and occipital pain since 8 months ago that was associated with restriction of neck movements, low to moderate grade fever, anorexia and weight loss followed by gradually progressive quadriparesis since 3 months ago. Neurological examination revealed spastic quadriparesis without cranial nerve palsy. MRI of the cervical spine revealed prevertebral and paravertebral abscess from clivus to C2/C3 level, which extended into the anterior epidural space at C1–C3 level, causing atlantoaxial dislocation. There was evidence of basilar invagination. The dislocated dens caused compression over the cervicomedullary junction. On this basis, a diagnosis of craniovertebral junction Pott's disease was made. The patient was given neck immobilisation with cervical collar, and antitubercular treatment was started. She showed significant improvement in her neurological deficit during follow-up.